Potent estrogen receptor β agonists with inhibitory activity in vitro, fail to suppress xenografts of endocrine-resistant cyclin-dependent kinase 4/6 inhibitor-resistant breast cancer cells - Marcho, Lynn M.; Coss, Christopher C.; Xu, Menglin; Datta, Jharna; Manouchehri, Jasmine M.; Cherian, Mathew A. (Frontiers in Oncology, 2025)
ObjectiveSeventy percent of newly diagnosed breast cancers are estrogen receptor-α positive and HER2/neu negative. First-line treatments incorporate endocrine therapy and cyclin-dependent kinase 4/6 inhibitors. However, therapy resistance occurs in most patients. Hence, there is an urgent need for effective second-line treatments. We previously showed that the potent estrogen receptor-β agonists, OSU-ERβ-12 and LY500307, synergized with the selective estrogen receptor modulator, tamoxifen, in vitro. Furthermore, we showed that these compounds inhibited endocrine-resistant and cyclin-dependent kinase 4/6-inhibitor-resistant estrogen receptor α-positive cell lines in vitro. Here, we used fulvestrant- and abemaciclib-resistant T47D-derived cell line xenografts to determine the efficacy of the combination of OSU-ERβ-12 and LY500307 with tamoxifen in vivo.ResultsDespite efficacy in vitro, treatments failed to reduce xenograft tumor volumes. Hence, we conclude that this treatment strategy lacks direct cancer cell-intrinsic cytotoxic efficacy in vivo.